A rare presentation of adult Bartter syndrome: a case report - B. S., Sreelekshmy; S. R., Ranjana; Dharman, Dhanya; Dharan, Shaiju S. (International Journal of Basic & Clinical Pharmacology, 2024)
Bartter syndrome (BS) is an inherited renal tubular disease. It is caused by a defective salt reabsorption in the thick ascending limb of loop of Henle. The term BS signify a group of renal disease which is the common divisor of hypokalemia and metabolic alkalosis. BS is categorized into 5 types based on the specific channel; type 1 is linked to gene SLC12A1, type 2 is linked to a gene KCNJ1, type 3 is linked to a gene called CICNKb while type 4 is linked to a gene BSND and type 5 is linked to CASR gene. This disorder is correlated with an increased antenatal and neonatal mortality. Here, a 61 years old female patient was presented with complaints of fever, myalgia, nausea, and cough for one day, decreased appetite and unable to do daily routine. Patient had conscious, oriented and afebrile. She had history of OAD, type 2 diabetes mellitus and hypertension. On hospital stay, she was started on IV calcium gluconate, potassium chloride, magnesium sulphate, antipyretics and other supportive measures. This case concludes the rarity of the BS. Correct diagnosis of BS is more expensive and not routinely available genetic testing. Therefore, the significance of diagnosing the case is more relevant.